(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today with increase in demand of electricity it is essential to have a good quality of power. As most of the load and power electronics equipment are nonlinear in nature many power quality problems like voltage sag ,voltage swell ,Harmonics, Voltage fluctuation, Flicker, gets introduced in System. UPQC(Unified Power Quality Conditioner)is one of the compensating device which consist of Shunt& Series Active Power Filter Cascaded with dc link capacitor. This paper present review of UPQC to enhance Quality of Power at distribution level Along with overview of different types of UPQC.